A Systematic Review of Risk Factor and Epidemiology of Cerebral Palsy - Sherly; Ronald (The Indonesian Journal of General Medicine, 2024)
Background: Cerebral palsy (CP), a neurodevelopmental disorder characterized by abnormalities in muscle tone, movement, and motor skills, is a common name attributed to developing brain damage. Although its clinical features are evident in the first years of life, the diagnosis of specific CP can be made after the period of 3 to 5 ages. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using Medline, Science Direct, Scopus and Embase, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: The high prevalence of CP, the low level of education among women, the inequalities in the distribution of income levels between regions, and the high level of consanguineous marriages in our country, especially in some regions.